Regulatory Network of Two Tumor-Suppressive Noncoding RNAs Interferes with the Growth and Metastasis of Renal Cell Carcinoma - Hui Zhou; Kun Tang; Haoran Liu; Jin Zeng; Heng Li; Libin Yan; Junhui Hu; Wei Guan; Ke Chen; Hua Xu; Zhangqun Ye (Elsevier, 2019)
Noncoding RNAs (ncRNAs) such as microRNAs (miRNAs) and long ncRNAs (lncRNAs) have been shown to function as pivotal regulators in the carcinogenesis of renal cell carcinoma (RCC). However, the functions and underlying mechanisms of most ncRNAs in RCC are still elusive, and the crosstalks of different layers of ncRNAs are seldom reported. Here we showed that miR-124 and maternally expressed gene 3 (MEG3) were both significantly reduced in RCC, and combined expression of miR-124 and MEG3 emerged as an independent prognostic factor in our RCC cohort. Overexpression of miR-124 or MEG3 inhibited cell proliferation, migration, and invasion in vitro, and restrained tumor growth in vivo. EZH2 knockdown induced the epigenetic silencing of miR-124 and MEG3 expression by H3K27me3. Besides, miR-124 directly targeted the TET1 transcript, and then the interaction resulted in the upregulation of MEG3. Furthermore, we demonstrated that MEG3 induced p53 protein accumulation, whereas p53 was a positive transcriptional regulator of the miR-124. In addition, tumor-suppressive PTPN11 was identified as a direct target of miR-124, as well as the MEG3- and p53-regulated gene. Our study identifies three crosstalks between miR-124 and MEG3, which provide a plausible link for these two ncRNAs in RCC. Both ncRNAs exert important antitumor effects in RCC pathogenesis and might serve as prognostic biomarkers and molecular therapeutic targets. Keywords: miR-124, MEG3, methylation, p53, renal cell carcinoma, EZH2, PTPN11, noncoding RNA